An overview of irrigation mosaics - Zahra Paydar; Freeman Cook; Emmanuel Xevi; Keith Bristow (Irrigation and Drainage, 2011)
Irrigation mosaics, involving discrete patches of irrigated land dispersed across the landscape, may offer an alternative to traditional large‐scale contiguous irrigation systems. This might be particularly attractive as a means of delivering improved social and economic opportunities for some rural and remote communities as well as better matching land use opportunities with landscape properties. The longer‐term environmental impacts of irrigation mosaics that may impair the sustainability of an irrigation project and the surrounding area are still largely unknown. However, there are findings from ecological and hydrological studies of other mosaics that can help with analysis of irrigation mosaics. This paper provides an overview of some biophysical aspects of irrigation mosaics, lessons learnt from other mosaics (e.g. landscape and farming system mosaics) and the potential environmental impacts of irrigation mosaics. Application of some tools for particular groundwater conditions indicates some of these impacts compared to traditional large‐scale systems. Irrigation mosaics could have both negative (more evaporation and water use, increased operational losses and costs) and positive (filtering surplus nutrients, enhanced biodiversity, preventing erosion, reduced area of impact around the irrigation area, lower water‐table rise) effects on the environment. Copyright © 2010 Commonwealth of Australia.

Comments on ‘Gas Permeability of Fractured Sandstone/Coal Samples Under Variable Confining Pressure’, Transport in Porous Media 83:333–347, 2010 - Freeman J. Cook (Transport in Porous Media, 2011)